‘Public-mindedness’ (gong gong) as an epistemic virtue in the political philosophies of the Shenzi shen zi and the Xunzi xun zi - O’Neill, Rory (Asian philosophy, 2026)
This article explores gong gong (‘public-mindedness’) as an epistemic virtue in two Warring States Chinese philosophical texts, the Shenzi and the Xunzi. The epistemic dimension of gong is born from an awareness of the narrowness of one’ s epistemic perspective. It represents an impartial and unbiased approach to governance. Gong is considered here alongside three epistemic virtues previously identified in the Chinese tradition: intellectual humility, open-mindedness, and knowledge abstinence. While there is some overlap between these and gong, there are important differences due in part to the political focus of the latter. There are also marked differences between its usage in the two texts. Gong in the Shenzi connotes a capacity to outsource the bases for political decisions to systems and processes external to one’ s epistemic faculties. The Xunzi, by contrast, maintains confidence in the cultivation of mind as a basis for governance, and gong represents a balanced and unbiased epistemic virtue.